Occurrence of Mesocestoides sp. (Cestoda: Mesocestoididae) in the Andean fox (Lycalopex culpaeus) - Angulo-Tisoc, José M. (2020)
In this work, we report Mesocestoides sp. parasiting one individual of Lycalopex culpaeus (Andean fox) captured from the Abra la Raya, Department of Cusco, Peru. The individual was necropsed in the Instituto Veterinario de Investigaciones Tropicales y de Altura (IVITA), Maranganí Headquarters. Numerous cestodes collected from the small intestine and morphologically analyzed. We provided a brief morphological description of Mesocestoides specimenes, and discuss concerning previous Mesocestoides species registered in Peru.